2008
DOI: 10.1021/je800158z
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Properties of Binary and Ternary Liquid Mixtures of 1-Propanol (1) + 2-Propanol (2) + Water (3) at Different Temperatures and Ambient Pressure (81.5 kPa)

Abstract: Excess molar volume, V m E , and excess partial molar volume, V i E , of the ternary mixtures of 1-propanol (1) + 2-propanol (2) + water (3) and of two binaries of 1-propanol (1) + water (3) and 2-propanol (2) + water (3) have been investigated from the density, F, measurements over the entire range of composition at temperatures (293.15, 303.15, 313.15, and 323.15) K and at ambient pressure (81.5 kPa). The limiting values of the excess partial molar volumes at infinite dilution, V i E,0 , and thermal expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…The application was tested on a set of 270 zeotropic and azeotropic systems of homogeneous binary solutions and 30 non‐homogeneous systems. In addition to the VLE data, values of the excess properties ( v E and h E ) have been used and, also, LLE data of the system studied, extracted from the literature,…”
Section: Results Of the Testmentioning
confidence: 99%
See 2 more Smart Citations
“…The application was tested on a set of 270 zeotropic and azeotropic systems of homogeneous binary solutions and 30 non‐homogeneous systems. In addition to the VLE data, values of the excess properties ( v E and h E ) have been used and, also, LLE data of the system studied, extracted from the literature,…”
Section: Results Of the Testmentioning
confidence: 99%
“…Undoubtedly, the results of the different methods qualify the data set chosen as being of good experimental quality, presenting a very low inconsistency. 2‐Propanol + water system at 101.32 kPa, iso ‐p VLE, Verhoeye and Schepper:The data of this azeotropic system were correlated with Eq. , with v E, and h E, data taken from the literature. The VLE data are represented graphically in Figure c, together with the curves produced by the consistency analysis.…”
Section: Results Of the Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the DMSO density with literature data [31][32][33][34][35][36][37][38] is presented in Figure 3. It can be observed that our data are consistent with the data reported by others authors.…”
Section: Densities Of Dmso + Amimclmentioning
confidence: 99%
“…Organic phase The new (liquid + liquid) equilibrium data was tested with correlations of Hand [22] and Othmer-Tobias [23], equations (12) and (13), respectively log…”
Section: Aqueous Phasementioning
confidence: 99%